Antithrombotic Therapy for Chronic Kidney Disease Patients With Concomitant Atrial Fibrillation and Coronary Artery Disease - Lee, Kuo-Hua; Ou, Shuo-Ming; Chu, Yuan-Chia; Lin, Yao-Ping; Tsai, Ming-Tsun; Tarng, Der-Cherng (Frontiers in Cardiovascular Medicine, 2021)
Background: Oral anticoagulants (OAC) plus antiplatelets is recommended for patients with atrial fibrillation (AF) and coronary artery disease (CAD) to reduce thromboembolism. However, there is limited evidence regarding antithrombotic therapy for patients with concomitant chronic kidney disease (CKD), AF, and CAD, especially those not undergoing percutaneous coronary intervention. We aimed to use real-world data assessing the efficacy and safety of antithrombotic regimens in this population. Methods: We used a single-center database of 142,624 CKD patients to identify those receiving antithrombotic therapy for AF and CAD between 2010 and 2018. Patients taking warfarin or direct OAC (DOAC) alone were grouped in the OAC monotherapy (n = 537), whereas those taking OAC plus antiplatelets were grouped in the combination therapy (n = 2,391). We conducted propensity score matching to balance baseline covariates. The endpoints were all-cause mortality, major adverse cardiovascular events, and major bleedings. Results: After 1:4 matching, the number of patients in OAC monotherapy and combination therapy were 413 and 1,652, respectively. Between the two groups, combination therapy was associated with higher risks for ischemic stroke (HR 2.37, CI 1.72–3.27), acute myocardial infarction (HR 6.14, CI 2.51–15.0), and hemorrhagic stroke (HR 3.57, CI 1.35–9.81). The results were consistent across CKD stages. In monotherapy, DOAC users were associated with lower risks for all-cause mortality, AMI, and gastrointestinal bleeding than warfarin, but the stroke risk was similar between the two subgroups. Conclusions: For patients with concomitant CKD, AF and CAD not undergoing PCI, OAC monotherapy may reduce stroke and AMI risks. DOAC showed more favorable outcomes than warfarin.